Understanding early childhood behavioral problems through parenting style–temperament typologies: a latent profile analysis - Zhou, Mingyue; Zhu, Dongmei; Guo, Shi; Zheng, Minxiao; Dang, Junhua (Frontiers in Psychology, 2025)
IntroductionThis study examined the combined effects of parenting style and child temperament on early childhood behavioral problems using latent profile analysis.MethodsA total of 5,138 valid questionnaires were collected from parents of children aged 3 to 6 years in Wuhan, China. Parenting styles, temperament traits, and behavioral problems were assessed using standardized instruments.ResultsFour distinct latent profiles were identified: Dysregulated Parenting–Rebellious Temperament, Unstable Parenting–Reserved Temperament, Supportive Parenting–Challenging Temperament, and Enriched Parenting–Compliant Temperament. Children in the Dysregulated Parenting–Rebellious Temperament group exhibited the highest rates of behavioral problems, whereas those in the Enriched Parenting–Compliant Temperament group showed the lowest. The results suggest that when children display more challenging temperamental traits, supportive parenting may be associated with lower behavioral problem prevalence. Conversely, children with more adaptable temperaments appear less susceptible to behavioral difficulties even in the context of less optimal parenting. Additionally, girls demonstrated significantly higher overall detection rates of behavioral problems than boys, and children with less-educated parents and lower household income exhibited greater behavioral problem prevalence.DiscussionThese findings underscore the importance of promoting positive parenting practices and accounting for individual temperament differences in early prevention efforts. Future research should employ longitudinal designs to validate and extend these findings.